2013
DOI: 10.1039/c3tc31545b
|View full text |Cite
|
Sign up to set email alerts
|

The influence of structure on the elastic, optical and dielectric properties of nematic phases formed from bent-core molecules

Abstract: The physical properties of the nematic phases formed by four bent-core oxadiazole based materials are reported. In particular, the splay (K11), twist (K22) and bend (K33) elastic constants, the birefringence and the dielectric anisotropy of the materials are described and the effect of chain length and the presence of fluoro-substituents at the outer phenylene group of the aromatic core structure on these parameters is determined. The birefringence and order parameter are found to be independent of the modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 45 publications
4
58
0
Order By: Relevance
“…It is likely that the formation of long range order and removal of the sponge-like structure in some materials and the absence of such a feature in others is related to the elastic constants of that mesogen. A study of the nature of the elastic constants in the nematic phase of our material has shown that this mesogen possesses relatively low splay, twist and bend elastic constants (K 11 = 8 pN, K 22 = 1 pN, K 33 = 3 pN close to N-DC phase transition) [33,34]. The standard elastic approach predicts that the saddle-splay elastic constant K 24 ≤ 2K 11 + K 22 or K 24 < K 22 whichever is smaller [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is likely that the formation of long range order and removal of the sponge-like structure in some materials and the absence of such a feature in others is related to the elastic constants of that mesogen. A study of the nature of the elastic constants in the nematic phase of our material has shown that this mesogen possesses relatively low splay, twist and bend elastic constants (K 11 = 8 pN, K 22 = 1 pN, K 33 = 3 pN close to N-DC phase transition) [33,34]. The standard elastic approach predicts that the saddle-splay elastic constant K 24 ≤ 2K 11 + K 22 or K 24 < K 22 whichever is smaller [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the nematic phase shows low splay (K 11 ), twist (K 22 ) and bend (K 33 ) elastic constants compared to other members in the homologues series [33,34]. It has low twist and bend elastic constants compared to calamitics [34].…”
Section: Properties Of the Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…(4). We referred to the general refractive indices nx and ny in the previous literatures for the Nb-LCD simulation [20,21]. The refractive indices of the VA-and the IPS-LCD were set to be ne = 1.70 and nz = 1.50.…”
Section: Methodsmentioning
confidence: 99%